Feedback System for Performance Appraisal of Teachers in Technical Institutes - Sharma, S. C.; Jha, Rameshwar (Journal of Engineering Education Transformations, 1991)
The role of teachers in technical institution is many fold. This can be fulfilled and justified only if the teachers are responsive and they understand the seriousness of teaching and the other duties in an institute. It is necessary that the teacher should know what is expected of him, how much is expected of him and what happens if he does better or worse than the expectation. Every teacher will be able to spell out clearly about his research activities publications, projects, consultancy. students activities, but no teacher will be able to say concretely on quality of, his/her teaching in the class room. Class room teaching and interaction with the students is very important aspect of the teachers study which has to be given the maximum weightage in the performance appraisal system. For this purpose each institute has to constitute a feed back unit with a very senior facility and reputed Professor as the head of that unit. A group of students of each course of class are to be invited for the feedback of the teachers about their teaching capacity and other related qualities, Students are the best judge for assessing the teachers performance in class room as it is the students in class who are involved while teachers are teaching.